Analisa Pengaruh Waktu Tahan Terhadap Cacat Warpage Pada Proses Injeksi Plastik Bahan Polypropylene (Pp) - Prasetya, Joko Dwi, Bambang Waluyo F.,ST., MT, Amin Sulistyanto, ST (2015)
Injection molding is a plastic forming process by way of melting the plastic material is injected into a mold (mold). Defects that often occur in injection molding products include a short shot, Sink mark, flash and warpage. The causes of warpage is affected by the injection pressure, mold temperature, melting and holding time in the plastic injection process (Huang and Tai, 2001). Therefore, the purpose of this study was to investigate the influence of the holding time of the occurrence of defects warpage of the results of injection molding products and to determine the proper holding time parameter to obtain the optimal product of injection molding. The initial step of making the mold (mold) with CNC milling machines and manufacture of cooling systems softooling type of conformal cooling channels. Toling soft system is made by mixing powdered aluminum and epoxy glue in the ratio 2: 1 channel conformal printed therein. The data collection method used is processing images with image capture using a 14 pixel camera and processed using software solidwork and warpage measurement with a dial indicator measuring devices that can be analyzed statistically and can be drawn to a conclusion. From the results of the study concluded that in this study generally increase the holding time making warpage percentage that increasingly smaller and smaller and even disappear and vice versa. Optimal holding time of this analysis, the holding time of 12.5 seconds. Keywords: injection molding, solidwork, dial indicators, hold time, warpage.